Does job support make workers happy? - Böckerman, Petri; Bryson, Alex; Kauhanen, Antti; Kangasniemi, Mari (Bonn, 2017)
"Using linked employer-employee data for Finland we examine associations between job design and ten measures of worker wellbeing. In accordance with Karasek's (1979) model we find positive correlations between many aspects of worker wellbeing and job control. However, contrary to the model, job demands have no adverse effects on worker wellbeing. We find a strong positive correlation between job support and all aspects of worker wellbeing that is independent of job controls and job demands, a finding that has not been emphasized in the literature. The effects are most pronounced in relation to supervisor support. We also find evidence of unemployment scarring effects: substantial experience of unemployment has long-term consequences for the wellbeing workers experience in their current jobs, even controlling for the quality of those jobs."